Production of trimeric SARS‐CoV‐2 spike protein by CHO cells for serological COVID‐19 testing. Issue 2 (11th November 2020) - Johari, Yusuf B.; Jaffé, Stephen R. P.; Scarrott, Joseph M.; Johnson, Abayomi O.; Mozzanino, Théo; Pohle, Thilo H.; Maisuria, Sheetal; Bhayat‐Cammack, Amina; Lambiase, Giulia; Brown, Adam J.; Tee, Kang Lan; Jackson, Philip J.; et al.
Abstract: We describe scalable and cost‐efficient production of full length, His‐tagged severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) spike glycoprotein trimer by Chinese hamster ovary (CHO) cells that can be used to detect SARS‐CoV‐2 antibodies in patient sera at high specificity and sensitivity. Transient production of spike in both human embryonic kidney (HEK) and CHO cells mediated by polyethyleneimine was increased significantly (up to 10.9‐fold) by a reduction in culture temperature to 32°C to permit extended duration cultures. Based on these data GS‐CHO pools stably producing spike trimer under the control of a strong synthetic promoter were cultured in hypothermic conditions with combinations of bioactive small molecules to increase yield of purified spike product 4.9‐fold to 53 mg/L. Purification of recombinant spike by Ni‐chelate affinity chromatography initially yielded a variety of co‐eluting protein impurities identified as host cell derived by mass spectrometry, which were separated from spike trimer using a modified imidazole gradient elution. Purified CHO spike trimer antigen was used in enzyme‐linked immunosorbent assay format to detect immunoglobulin G antibodies against SARS‐CoV‐2 in sera from patient cohorts previously tested for viral infection by polymerase chain reaction, including those who had displayed coronavirus disease 2019 (COVID‐19) symptoms. The antibody assay, validated to ISO 15189 Medical Laboratories standards, exhibited a specificity of 100% and sensitivity of 92.3%. Our data show that CHO cells are a suitable host for the production of larger quantities of recombinant SARS‐CoV‐2 trimer which can be used as antigen for mass serological testing. Abstract : High‐level production of the very difficult‐to‐express SARS‐CoV‐2 spike protein in a native, trimeric format is described. The authors detail optimized transient expression in both HEK and CHO cells yielding up to an 11‐fold increase in titer. Synthetic promoters paired with stable cell line generation, hypothermic culturing and bioactive small molecules permitted expression up to 53 mg/L. Subsequent purification and product characterization resulted in trimeric spike being utilized for detection of anti‐spike IgG antibodies in sera from COVID‐19 patient cohorts.